Factors Influencing Customers Buying Behavior (Global Journal of Management and Business Research, 2016)
Customer buying behavior is a process by which consumers identify their needs, collect information, evaluate alternatives, and make the purchase decision. It is a series of choices made by a consumer prior to making a buying that begins once the customer has established a willingness to buy. Many of the research papers argue about customer buying behavior. The marketer attempts to influence each of these decisions by supplying information that may shape the consumers evaluation. The Six stages of the consumer buying behavior process are Problem Recognition, Information search, Evaluation of Alternatives, Purchase Decision, Purchase, Post-Purchase Evaluation. The research paper attempts to find the various determinants of customer buying behavior at Srinivasa Motors. Results are finding with using of various statistical tools. This research paper is useful to the marketers to understand the interest of the customers. It also can help to boost their marketing strategy.
Keywords: consumer; customer buying behavior; marketing strategy; purchase decision